2018
DOI: 10.1186/s12905-018-0685-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion is associated with less stress and depression and greater attention and brain response to affective stimuli in women managers

Abstract: BackgroundWomen have been assuming more responsibilities and higher positions in major companies, which exposes them to high levels of stress. Higher perceived work stress is related to higher emotional reactivity. Difficulties with emotional regulation can lead to anxiety and mood disorders, which are more prevalent in women than men. Indeed, women leaders are more likely to experience emotional fatigue than men due to excessive empathy. Our aim was to evaluate the associations between self-compassion (SC) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
3
11
0
4
Order By: Relevance
“…Being mindful enables people to be more aware and accepting of their experiences of the present moment, leading to reductions in stress levels and other negative outcomes (Colgan et al, 2019 ; Creswell & Lindsay, 2014 ). Moreover, as supported by previous findings (Pires et al, 2018 ), people with higher self-compassion scores report greater mindfulness and sensitivity to emotional stimuli.…”
Section: Discussionsupporting
confidence: 85%
“…Being mindful enables people to be more aware and accepting of their experiences of the present moment, leading to reductions in stress levels and other negative outcomes (Colgan et al, 2019 ; Creswell & Lindsay, 2014 ). Moreover, as supported by previous findings (Pires et al, 2018 ), people with higher self-compassion scores report greater mindfulness and sensitivity to emotional stimuli.…”
Section: Discussionsupporting
confidence: 85%
“…The main function of the precuneus is related to “perspective-taking” (Lamm et al, 2011 ), which allows subjects to generate empathy not only through direct observation but also through imaging other people’s emotions. Furthermore, the precuneus is also involved in the identification and processing of emotional valences in others (Pires et al, 2018 ). Therefore, we can make an inference in the current study: when patients with cLBP are watching photos, the precuneus with abnormal activities transfers the wrong evaluation information to the executive network, thus affecting the ability to empathize.…”
Section: Discussionmentioning
confidence: 99%
“…Eby and colleagues’ (2019) review showed that individuals who most benefited from mindfulness training and its related outcomes, like self-compassion, were those who experienced higher levels of stress. Additionally, they reported that mindfulness trainings were beneficial for individuals who were employed in jobs that have high demands, such as the military and police, practicing psychologists (Eriksson et al, 2018), healthcare workers (Dev et al, 2020; Vaillancourt & Wasylkiw, 2019), and women managers from the cosmetics sector (Pires et al, 2018).…”
Section: A Practical Guide To Nurture Workplace Self-compassionmentioning
confidence: 99%